Conditions for the effective use of dialogue and discussion teaching technologies in higher education - Olena Druhanova (Scientific notes of the pedagogical department, 2023)
The purpose of the article is to analyze and characterize the conditions that provide for the eﬀective use of dialogue and discussion technologies to ensure quality learning outcomes for modern students studying in higher education. The article proves that the eﬀectiveness of introducing dialogue and discussion technologies into the educational process of a modern higher education institution is closely related to the level of general and professional competencies of teachers who conduct classes. Among such competences are the following: the ability to search for supporting motives or issues of concern to modern higher education students; educational and scientific problems that can help to form the personal meaning of the material being studied. The list of necessary competences that guarantee the ability to eﬀectively use dialogue and discussion technologies also includes the ability of the teacher to ensure that the student is motivated to actively interact with all participants in the educational process, to create situations for them in which they feel their own success, intellectual capacity, etc. Important and necessary conditions also include: the teacher’s ability to manage the dialogue, his or her ability to program various options for the development of dialogue storylines; design diﬀerent ways of interaction between dialogue participants, foresee and distribute their possible roles; simultaneously monitor and timely adjust the purpose, time, results (analysis of successes or faiures) of mutual learning activities, etc. A promising area for further research is the analysis and characterization of the conditions associated with a higher education student’s readiness to actively participate in dialogue.